Gib Mihăescu – universul prozei scurte - Andrei Baciu (Revista de Istorie și Teorie Literară)
The most valuable part of Gib Mihăescu’s work consists of his short stories. As it is often and legitimally claimed, no other Romanian writer has ever described the avatars of the obsession as well as him. Yet, what was not noticed about his short stories is the fact that, beyond the fixation, be it erotical or of another nature, that animates Mihăescu’s characters, the powerful fascination they exert upon the reader lies in the super-natural correspondence between the individuals’ inner experiences and their exterior environment. This, under the conditions that behind this uncanny relation there is a real modern existential thesis of the absurd: because of a metaphysical conspiracy – nota bene, as unmetaphorical as possible – the protagonists are inexorably driven towards the most tragic endings.